Optimization of Antibacterial Activity in Tibetan Swine α-Helix Peptide TP by Site-Directed Mutagenesis - Li, Guoyu; Yuan, Xiaojie; Chen, Hongyu; Li, Bowen; Shao, Changxuan; Zhu, Yongjie; Lai, Zhenheng; Shan, Anshan (Frontiers in Microbiology, 2022)
Antimicrobial peptides (AMPs) have attracted extensive attention because of their broad-spectrum antibacterial activity and low level of induced bacterial resistance. However, the development of some natural AMPs does not consider the perfect balance of structural characteristics, resulting in some empirical and controversial practices still existing. In order to further explore and complete the relationship between parameters and function of α-helix peptide. In this study, we select natural amphiphilic AMPs TP from Tibetan swine to study the effects of systematic-mutations at ith and i+4th hydrogen bond formation sites on activity and selectivity. The target peptide TP(i+4) 1&2&5 with modification of two pairs of positively charged amino acids and a pair of hydrophobic amino acids shows excellent antibacterial ability and the best therapeutic index (TI=64) in vitro. At the same time, target peptide TP(i+4) 1&2&5 remained active in the presence of physiological salts and serum. The results of fluorescence, flow cytometry and electron microscopy showed that the optimized sequences showed good antibacterial activity by membrane infiltration and membrane destruction. The potential of TP(i+4) 1&2&5 in vivo was tested in a mouse peritonitis model. Bacterial burdens in liver, kidney and lung after TP(i+4) 1&2&5 was significantly decreased compared to infection group. Overall, these findings contribute to the design and optimization of antimicrobial peptides with high activity and low toxicity, and may accelerate the clinical application of antimicrobial peptides.